Optimization of light intensity and color temperature in the cultivation of Chlorella vulgaris culture using the Surface Response Method - Marcelinus Christwardana; H. Hadiyanto; Wahyu Zuli Pratiwi (BIORE Scientia Publisher, 2022)
Microalgae have an important role as a source of biomass in producing energy. One type of microalgae that has the potential to be developed is Chlorella vulgaris. Several factors that affect the growth and biomass production of Chlorella vulgaris microalgae are color temperature and light intensity because they play an important role in the photosynthesis process. This study aims to influence the effect of light and color temperature and optimize these parameters using Response Surface Methodology (RSM). Two independent variables were varied: light intensity 200, 400, 600, 800, 1000 lux and color temperature 3000, 4000, 5000, and 6000 K. The results showed that the average value of Chlorella vulgaris growth was higher along with higher light intensity. At a color temperature of 4000 K, the highest biomass yield and the most negligible biomass production were found at 6000 K. At a color temperature of 4000 K, it is feasible to apply it as an alternative lighting source in the production of Chlorella vulgaris. The combination of light intensity and color temperature shows that the specific growth rate and doubling time have opposite trends where high values produce low values and vice versa. Growth in dark conditions, the specific growth rate was 0.0026 day-1, and the optimal light intensity at 600 lux treatment. ANOVA evaluation showed that color temperature greatly affected growth. Based on the optimization, the optimal specific growth rate of 00751day-1 with the conditions of light intensity and color temperature of 556 lux and 4152 K, respectively.